Mandibular cortical bone height in bruxism patients based on gonion and antegonial index - Fidela D. Aziza; Setyawan Bonifacius; Lusi Epsilawati (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine differences in the height of the mandibular cortical bone in patients with bruxism and those who were not.Material and Methods: This study used an analytic method with a cross-sectional approach. Samples taken were divided into two groups, each with 30 digital panoramic radiograph samples of people with bruxism and those not with bruxism. The study was conducted by measuring the height of the mandibular cortical bone on digital panoramic radiograph based Gonion Index (GI) and Antegonial Index (AI) using Image J application.Results: Bruxism patients aged 21-30 years were 27 people and aged 31-40 years were 3 people, with 12 male samples, and 18 female samples. Samples of non-bruxism patients aged 21-30 years were 28 people and aged 31-40 years were 2 people, with 15 male samples and 15 female samples.Conclusion: There was no difference in the height of the mandibular cortical bone in patients with bruxism and non-bruxism patients based on GI and AI.